Indonesian Traditional Games as a Medium for Instilling Moral Values in Students: A Literature Review - Arif Samsurrijal (PT. Islamic Research Publisher, 2022)
Children are the heirs of a nation’s future. Therefore, they need to be equipped with education, including character education. Character education can serve as a safeguard, protecting children from negative influences amid the rapid advancement of technology today. This article aims to describe how Indonesian traditional games can function as a medium for instilling character values in students or children. Indonesia, with its rich ethnic and cultural diversity, possesses a wide variety of traditional games that embody noble values inherited from previous generations. This study is a literature review (library research) that utilizes secondary data. The data collection technique employed is documentation, while the data analysis technique used is descriptive-inductive. The findings indicate that Indonesia has numerous traditional games from various regions. In addition, these games contain valuable character-building values that align well with the nature of children, whose world is fundamentally one of play.